Ανάλυση σεισμικής τρωτότητας λιμενικού κρηπιδότοιχου πολλαπλών τεμαχών : Εφαρμογή στο λιμάνι του Πειραιά - Αϊδίνης, Δημήτριος (Σχολή Πολιτικών Μηχανικών, 2015)
In this diploma thesis, the effort is concentrated at the study of dynamic response of a typical caisson-type quay wall section at Piraeus port in Greece and the development of vulnerability curves based on numerical analysis. Utilizing the Byrne's elastoplastic constitutive model, an effective stress dynamic analysis is performed using as seismic excitation fifteen recorded motions of the seismic environment throughout the world. These excitations are applied to three different types of the backfill soil regarding the relative density (Dr). Primarily, the results emphasize the role of relative density and time history of excitation on the horizontal displacement and the tilt of a typical caisson-type quay wall. Supplementary results demonstrate secondary deformations of a caisson-type quay wall, like the settlement of the backfill soil and the heave of the soil surface at the sea bottom, in front of the toe of the wall. The excess pore water pressure, positive or negative, build-up during shaking is also examined in extent, shedding light on the liquefied or non-liquefied regions of the soil profile and the ensuing deformation of the adjacent quay-wall, in sight of interaction. The numerical modeling is performed using the two-dimensional finite element program Plaxis2D in order to extract the results that are of our interest in this thesis, either it is the time histories of some variables or the ultimate values of others.